Trauma-focused EMDR for Personality disorders among Outpatients (TEMPO): study protocol for a multi-centre, single-blind, randomized controlled trial - Hofman, Simon; Hafkemeijer, Laurian; de Jongh, Ad; Starrenburg, Annemieke; Slotema, Karin (Current controlled trials in cardiovascular medicine, 2022)
Background Existing recommended treatment options for personality disorders (PDs) are extensive and costly. There is emerging evidence indicating that trauma-focused treatment using eye movement desensitization and reprocessing (EMDR) therapy aimed at resolving memories of individuals’ adverse events can be beneficial for this target group within a relatively short time frame. The primary purpose of the present study is to determine the effectiveness of EMDR therapy versus waiting list in reducing PD symptom severity. Furthermore, the effects of EMDR therapy on trauma symptom severity, loss of diagnosis, personal functioning, quality of life, and mental health outcomes will be determined. In addition, the cost-effectiveness of EMDR therapy in the treatment of PDs is investigated. Moreover, predictors of treatment success, symptom deterioration and treatment discontinuation will be assessed. Lastly, experiences with EMDR therapy will be explored. Method In total, 159 patients with a PD will be included in a large multicentre single-blind randomized controlled trial. The Structured Clinical Interview for DSM-5 Personality Disorders will be used to determine the presence of a PD. Participants will be allocated to either a treatment condition with EMDR therapy (ten biweekly 90-min sessions) or a waiting list. Three months after potential treatment with EMDR therapy, patients can receive treatment as usual for their PD. All participants are subject to single-blinded baseline, post-intervention and 3-, 6- and 12-month follow-up assessments. The primary outcome measures are the Assessment of DSM-IV Personality Disorders and the Clinician-Administered PTSD Scale for DSM-5. For cost-effectiveness, the Treatment Inventory of Costs in Patients with psychiatric disorders, EuroQol-5D-3L, and the Mental Health Quality of Life Questionnaire will be administered. The PTSD Checklist for DSM-5, Brief State Paranoia Checklist and Difficulties in Emotion Regulation Scale will be used to further index trauma symptom severity. Type of trauma is identified at baseline with the Childhood Trauma Questionnaire-SF and Life Events Checklist for the DSM-5. Personal functioning and health outcome are assessed with the Level of Personality Functioning Scale-BF 2.0, Outcome Questionnaire-45 and Mental Health Quality of Life Questionnaire. Experiences with EMDR therapy of patients in the EMDR therapy condition are explored with a semi-structured interview at post-intervention. Discussion It is expected that the results of this study will contribute to knowledge about the effectiveness, and cost-effectiveness of trauma-focused treatment using EMDR therapy in individuals diagnosed with a PD. Follow-up data provide documentation of long-term effects of EMDR therapy on various outcome variables, most importantly the reduction of PD symptom severity and loss of diagnoses. Trial registration Netherlands Trial Register NL9078 . Registered on 31 November 2020